March 27, 2017

Post a New Question

Posted by on .

(a) Given that A= 3i - j + 2k and
B=2i + 3j - k find A x B

(b) if A= i + j, B= 2i - 3j + k and
C= 4j - 3k
find (i) (AxB)x C
(ii) Ax(BxC)

  • Help on Vectors & Geometry - ,

    I will do one. These are much easier to do as matrix multipication on your calc, I would learn to do that.
    AxB= (3i-j+2k)x(2i+3j-k)
    = 3*3ixj-3ixk-2jxi+jxk+4kxi+6kxj
    well, ixj=k
    kxi=j (and the opposite order means -)
    AxB= 9k+3j+2k+i+4j-6i
    check that, and combine terms.

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question